Antimicrobial and Cytotoxic Activities of Lepidium latifolium L. Hydrodistillate, Extract and Its Major Sulfur Volatile Allyl Isothiocyanate. Issue 4 (20th March 2019) - Blažević, Ivica; Đulović, Azra; Maravić, Ana; Čikeš Čulić, Vedrana; Montaut, Sabine; Rollin, Patrick
Abstract: The cultivated Lepidium latifolium L. was investigated to decipher its glucosinolate profile, antimicrobial, and cytotoxic activities. HPLC/ESI‐MS analyses of the intact glucosinolates and GC/MS analysis of their hydrolysis products showed the presence of sinigrin (1 ), glucocochlearin (2 ), glucotropaeolin (3 ), and 4‐methoxyglucobrassicin (4 ). Hydrodistillate, extract, and allyl isothiocyanate, the main volatile resulting from sinigrin degradation, showed antimicrobial activity against all eleven tested pathogenic and food spoilage bacteria and fungi, with highest effect observed against Candida albicans with MIC50 8 and 16 μg/mL. Hydrodistillate and extract showed the best cytotoxic activity on bladder cancer UM‐UC‐3 cell line during an incubation time of 24 h (IC50 192.9 and 133.8 μg/mL, respectively), while the best effect on glioblastoma LN229 cell line was observed after 48 h (IC50 110.8 and 30.9 μg/mL, respectively). Pure allyl isothiocyanate displayed a similar trend in cytotoxic effect on both cell lines (IC50 23.3 and 36.5 μg/mL after 24 h and 48 h, respectively). Abstract :